Investigating Environmental Impact Assessment (EIA) In Early Studies (Zero-Phase) to Prevent Delay in Operation of Construction Projects - Iraj Jalali; S. Mahammad Poorhashemi; Alireza Mirjalili (Civil Engineering Journal, 2018)
Delay in project execution is one of the outmost problems that lead to delay to operation and subsequently, early structural erosion or financial supply disturbance, etc. Delay is fallen into several categories and each category has its own specific origin. However, in the present paper, environmental factors causing delay to projects are investigated. Delay to Construction Projects operation can be prevented by embedding environmental studies, namely environmental impact assessment (EIA) in initial studies. Given that environmental events cannot be predicted and we can only rely on statistic reports of previous periods, the effect of embedding such assessment in projects is so useful that every manger is convinced to make use of this assessment in study phase. The research results revealed that it is necessary to present EIA in initial studies to prevent delay to Construction Projects operation. In the following, given to the necessity of checklist, the quality of the designed checklist was investigated. Finally, the checklist was implemented and checked. In this study, each of the research questions was separately tested.